2023
DOI: 10.3389/fcomp.2023.1141649
|View full text |Cite
|
Sign up to set email alerts
|

A review of intelligent interactive learning methods

Aru Ukenova,
Gulmira Bekmanova

Abstract: The development of intelligent interactive learning approaches has received a lot of attention in recent years due to the trend of incorporating intelligent algorithms. Intelligent interactive education tools have a significant positive impact on user engagement, motivation, and social outcomes. This study attempts to explore the existing models, methods and technologies of intelligent interactive learning including virtual and augmented reality. The method of the current study was a semi-systematic literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Interactive approach is based on students' active participation (Fan & Li, 2023;Seo et al, 2021) and incorporates AI technologies (Ukenova & Bekmanova, 2023). It is suggested that the interactive approach enhances teaching with AI due to a number of advantages which refer to students' engagement instead of passive receiving of educational material; organisation of collaborative activities; customisation of learning based on students' individual needs and psychological characteristics; increasing motivation to learning and future professional activities.…”
Section: Discussionmentioning
confidence: 99%
“…Interactive approach is based on students' active participation (Fan & Li, 2023;Seo et al, 2021) and incorporates AI technologies (Ukenova & Bekmanova, 2023). It is suggested that the interactive approach enhances teaching with AI due to a number of advantages which refer to students' engagement instead of passive receiving of educational material; organisation of collaborative activities; customisation of learning based on students' individual needs and psychological characteristics; increasing motivation to learning and future professional activities.…”
Section: Discussionmentioning
confidence: 99%
“…The healthcare domains covered were mental care (8), obesity (7), perception disability (4), and others. The types of games used were predominantly mobile applications (21), whereas fewer studies used social media (2), virtual reality (2), and other platforms. The health outcomes studied included activity (6), diet (3), depression (3), memory (3), and others.…”
Section: General Characteristics Of the Literaturementioning
confidence: 99%
“…Digital innovations have technologically revolutionized health interventions and health education, driving a trend during the coronavirus disease 2019 pandemic toward the use of game elements to engage audiences both virtually and in person, reinforcing knowledge, behaviors, and attitude changes [ 1 ]. Gaming elements have facilitated internet-based interventions to connect with audiences in diverse ways, employing virtual reality, augmented reality, chatbots, and artificial intelligence [ 2 ]. Even post-pandemic, the appeal of video training and internet interventions has not waned, and these modalities have remained attractive for both audiences and providers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%